2020
DOI: 10.1002/jcsm.12584
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related decline of interferon‐gamma responses in macrophage impairs satellite cell proliferation and regeneration

Abstract: Background Impaired muscle regeneration and increased muscle fibrosis are observed in aged muscle accompanied by progressive loss of muscle mass (sarcopenia). However, the underlying mechanism is still unclear. Methods The differentiated expressed genes in young and aged muscles after acute injury by cardiotoxin were identified by RNA-sequence analysis. Single-cell RNA-sequence analysis was used to identify cell clusters and functions in young muscle after acute injury, and flow cytometry analysis and sorting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 51 publications
4
61
1
Order By: Relevance
“…Consistent with recent reports, we found that aged mice displayed marked defects in regenerating myofiber number and size (Blanc et al, 2020;Patsalos et al, 2018;Rahman et al, 2020;Zhang et al, 2020), but RvD1 treatment had minimal impact on this response. Aging is also well-established to limit recovery of muscle function following injury, due at least in part to an accumulation of fibrotic tissue during muscle regeneration (Rahman et al, 2020;Zhang et al, 2020).…”
Section: Systemic Treatment Of Aged Mice With Rvd1 Has Previouslysupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with recent reports, we found that aged mice displayed marked defects in regenerating myofiber number and size (Blanc et al, 2020;Patsalos et al, 2018;Rahman et al, 2020;Zhang et al, 2020), but RvD1 treatment had minimal impact on this response. Aging is also well-established to limit recovery of muscle function following injury, due at least in part to an accumulation of fibrotic tissue during muscle regeneration (Rahman et al, 2020;Zhang et al, 2020).…”
Section: Systemic Treatment Of Aged Mice With Rvd1 Has Previouslysupporting
confidence: 92%
“…Consistent with recent reports, we found that aged mice displayed marked defects in regenerating myofiber number and size (Blanc et al, 2020;Patsalos et al, 2018;Rahman et al, 2020;Zhang et al, 2020), but RvD1 treatment had minimal impact on this response. Aging is also well-established to limit recovery of muscle function following injury, due at least in part to an accumulation of fibrotic tissue during muscle regeneration (Rahman et al, 2020;Zhang et al, 2020). Indeed, we found that aged mice showed marked deficits in recovery of strength due to both reduced abilities of aged muscle to recover its pre-injury size as well as maladaptive tissue remodeling that further impaired relative contractile function.…”
Section: Systemic Treatment Of Aged Mice With Rvd1 Has Previouslysupporting
confidence: 92%
“…TNF) observed in muscles of elderly patients (81 years old) male compared to young patients (23 years old) [99], and in muscles from aged C57BL/6J male mice [100]. Interestingly, following cardiotoxininduced injury, aged male C57BL/6J mice (24 months) showed decreased infiltration of macrophages into damaged muscle [101], which was associated with decreased chemokine secretion (particularly interferon-gamma inducible protein-10). This is similar to the delayed inflammatory infiltration previously observed with crosstransplantation young-old studies in aged female C57BL/6J mice [97], suggesting that the ageing microenviroment impacts chemotaxis [102].…”
Section: Macrophages In Musculoskeletal Injury Repair and Ageingmentioning
confidence: 95%
“…On the one hand, this classification is not entirely consistent with the ideas of Mills who defined macrophages based on their function, and the macrophage types defined in these two ways actually have different gene signatures as shown by comparing transcriptomes between the M1/M2 and classically/alternatively activated types ( 39 , 40 ). On the other hand, it is an oversimplification to describe the spectrum of macrophage subsets using only two categories ( 34 , 41 43 ), which neglect the diversity of macrophages in distinct tissues and conditions ( 33 , 44 , 45 ). Some suggest that M1 and M2 are more like two extremes of macrophage polarization and that the observation of the complete process is limited by experimental methods ( 46 ).…”
Section: Macrophages and Heart Regeneration And Repairmentioning
confidence: 99%